Foot soft tissue myopericytoma: Case-report and review. (2017) - Provenzano, D.; Lo Bianco, S.; Belfiore, M.; Buffone, A.; Cannizzaro, M.A.
Highlights: Myopericytoma is a rare tumor of deep soft tissues. Small tumefying at the level of the plantar region, between the 2nd and 3rd toe of the right foot. Neoformation of 0.6 cm in diameter, well circumscribed, capsulated and with free resection margins. The immunohistochemical profile was consistent for positive alpha-actin and negative desmine. Abstract: Introduction: Myopericytoma is a rare tumor of deep soft tissues, originating from pericytes and characterized by numerous thin walled blood vessels. Case report: We report a case of myopericytoma found at the level of the second toe of the right foot. A patient came to the Endocrinology Surgery Department of Catania Polyclinic because of a presence of a small swelling in the plantar region, between the 2nd and 3rd toe of the right foot. At the anatomopathological examination, the escalated lesion showed a neoformation of 0.6 cm in diameter, well circumscribed, capsulated, with myopericytoma diagnosis. Discussion: Its histopathological appearance is similar to myofibromatic lesions from glomic and angiomyoma tumors. It is a rare tumor that affects all ages with a peak after 50 years 3. The most frequent localization is at the lower extremities, particularly in soft subcutaneous tissues, but can rarely occur in other sites. Conclusion: At the anatomopathological evaluation, the immunohistochemical examination for the correct formulation of the diagnosis is essential and an adequate surgical excision is important.